INDONESIAN CULTURAL IDENTITY IN SOCIAL MEDIA NETWORKS: A CRITICAL DISCOURSE ANALYSIS ON INSTAGRAM OF GEN Z USERS - P, Prisma Hanindita Inggit; Supriadi, Idris; N, Efraim Hamonangan; Sari, Yunita (MSJ : Majority Science Journal, 2024)
Among the mediums that can be used to express cultural identity is social media. The purpose of this study is to examine how Indonesian culture is presented and how to preserve it, and how to express Indonesian cultural identity on the Instagram social media platform. This research was conducted using a qualitative research method in the form of a critical discourse analysis method. Initial research data through interviews with generation Z Instagram users and secondary data in the form of literature and observations. The results showed that Instagram social media can be a means to express Indonesian cultural identity. However, there are still many Instagram users who are not wise in using social media. This can be seen from the many negative comments made by Instagram users. This is contrary to Indonesian culture which is famous for its politeness. Therefore, it requires mutual awareness to utilize social media wisely. Cultural content that is interesting and relevant to everyday life can be a concrete step in expressing Indonesian cultural identity in the digital era.